1994
DOI: 10.1007/bf00972064
|View full text |Cite
|
Sign up to set email alerts
|

The consideration of cultural factors in the research of elder mistreatment with an in-depth look at the Japanese

Abstract: Within the context of elder mistreatment, little attention has been paid to ethnicity and cultural factors as independent or causal variables. Focusing on the Japanese as an example, this paper explores cultural factors that may be associated with family conflict and elder mistreatment, including the use of silence as an extreme form of punishment. Also explored are the interrelationships of dependency (amae), holding back (enryo), and being in the way (jama); of social obligation (giri), personal indebtedness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…Japanese culture, too, emphasizes family over self, the (collective man) over the individual (Roland 1988). To these groups, therefore, preferred sources of assistance are found in the family and community and not among outsiders, such as police and helping professionals (Tomita 1994). Also, these results support the work of Kaneko & Yamada (1990) in that manifestations of bad treatment in the opinion of Japanese-American respondents included avoiding or excluding elders.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Japanese culture, too, emphasizes family over self, the (collective man) over the individual (Roland 1988). To these groups, therefore, preferred sources of assistance are found in the family and community and not among outsiders, such as police and helping professionals (Tomita 1994). Also, these results support the work of Kaneko & Yamada (1990) in that manifestations of bad treatment in the opinion of Japanese-American respondents included avoiding or excluding elders.…”
Section: Discussionsupporting
confidence: 78%
“…Tomita (1994), considering the Japanese, echoed Brown's focus on cultural factors that contribute to variability in the definition of elder mistreatment. For example, despite the overt absence of conflict within Japanese families, silence and avoidance, while subtle, may be used as extreme forms of punishment, and may be as emotionally devastating as physical abuse.…”
Section: Differences By Ethnic Groupmentioning
confidence: 99%
“…Consistent with previous studies (Anetzberger et al, 1996; Tomita, 1994), silence was commonly perceived as an extreme form of psychological humiliation or punishment in the Chinese and Korean communities and had even more impact due to cultural expectations. To illustrate, a Chinese participant made the following comment:

When worse come to worse, seniors have to suffer all the verbal abuse.

…”
Section: Resultssupporting
confidence: 89%
“…Derived largely from working with older Whites, existing measures of EM have failed to capture varying cultural contexts or to explore the breadth of its socially embedded manifestations. For example, silence is commonly employed as an extreme form of psychological humiliation or punishment in many Asian cultures (Anetzberger, Korbin, & Tomita, 1996; Tomita, 1994). Yet, current standardized measures of mistreatment would fail to detect abuse of this nature.…”
Section: Background and Related Literaturementioning
confidence: 99%
“…The findings of numerous studies across various cultural groups suggest that ethnic background, and such other cultural factors as sexual orientation and gender socialization, may result in differences in how victims define elder abuse and their help-seeking behavior (Brown, 1989;Griffin, 1994;Tomita, 1994;Nagpaul, 1997;Chang & Moon, 1997;Sanchez, 1999;Hudson & Carlson, 1999;Moon, Tomita & Jung-Kamei, 2001). For example, Moon and Williams (1993) found that Korean-American elders have a narrower definition of elder abuse and a greater reluctance to seek help than either Caucasian Americans or African-Americans.…”
Section: The Victim's Perspectivementioning
confidence: 99%